Innovative solution principles of wave problems in horizontaly layered medias - Štrukelj, Andrej (Acta geotechnica Slovenica, 2006)
The paper presents engineeringly reasonable transformation of surface displacements of horizontally layered half-space. The latter shows in the half-space present types of waves. It is shown that surface waves are expressed through residuums in poles of the integrand and the volume waves are expressed as integrals along corresponding branch cuts. The singularity which always appears in the basic singular solution in elastodynamics is in this case exactly excluded. In the second part of the paper the behaviour of Stonely waves is investigated in greater detail. It is shown that in the case of layers of finite thickness their appearance and velocities depends not onlyon the material characteristics of neighbouring layers but also on their thickness.
Keywords: geomehanika; Greenova funkcija; mehanika tal; slojeviti polprostor; valovi